2016
DOI: 10.1016/j.jpge.2016.02.001
|View full text |Cite
|
Sign up to set email alerts
|

Hepatocellular Carcinoma in Chronic Hepatitis B Patients on Third Generation Nucleos(t)ides Analogs: Risk Factors and Performance of a Risk Score

Abstract: ObjectiveTo investigate hepatocellular carcinoma (HCC) incidence, risk factors and the performance of baseline REACH-B risk score in a Portuguese chronic hepatitis B (CHB) population on antiviral therapy.MethodsRetrospective study of CHB patients who were treated with tenofovir or entecavir for at least 12 months. Multivariate analysis was performed to identify factors associated with HCC. The Kaplan–Meier method was used to estimate the cumulative incidence of HCC at 1, 3 and 5 years on therapy. The performan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…Moreover, the predictive performance of the REACH-B model was lower both overall and in antiviral subgroups. is contradicted the findings of Magalhaes et al [30] and Chen et al [31], both of whom reported that the REACH-B model maintained its predictive power in the background of receiving antiviral therapy. is may be because of the insufficient number of studies included in this paper, and more data on the predictive performance of the REACH-B model were needed for metaanalysis research.…”
Section: Discussionmentioning
confidence: 58%
“…Moreover, the predictive performance of the REACH-B model was lower both overall and in antiviral subgroups. is contradicted the findings of Magalhaes et al [30] and Chen et al [31], both of whom reported that the REACH-B model maintained its predictive power in the background of receiving antiviral therapy. is may be because of the insufficient number of studies included in this paper, and more data on the predictive performance of the REACH-B model were needed for metaanalysis research.…”
Section: Discussionmentioning
confidence: 58%
“…Only one study, for which the cohort was based on the TDF registration trial, defined the degree of liver fibrosis/cirrhosis by histopathology 21 ; while the other 18 studies allowed clinical or imaging‐based diagnosis for cirrhosis. HCC incidence rates varied widely across these studies 7,8,10,18,21–35 ; in general, however, the 5‐year cumulative incidence increased from patients without cirrhosis (0.5–6.9%) to patients with compensated (4.5–21.6%) and decompensated cirrhosis (36.3–46.5%) (Fig. 2 ) .…”
Section: Resultsmentioning
confidence: 96%
“…5‐year cumulative probability of hepatocellular carcinoma under long‐term tenofovir or entecavir treatment in patients with chronic hepatitis B according to cirrhosis status. 1A (upper panel): without cirrhosis 7, 8, 10, 21–27, 30–33, 35 ; 1B (middle panel): with compensated cirrhosis 18, 21, 26, 28–30, 34 ; 1C (lower panel): with decompensated cirrhosis 26, 29 . (a) The 5‐year cumulative incidence, which was not shown in the original article, was estimated according to HCC events and patients at risk with the context.…”
Section: Resultsmentioning
confidence: 99%